Evaluation of the effect of a gel made with amniotic fluid formulation on the healing of diabetic foot ulcers: A triple-blind clinical trial - Niami, Fatemeh; Molavynejad, Shahram; Hemmati, Ali Asghar; Bijan Nejad, Darioush; Yazdanpanah, Leila; Maram, Nader Shakiba; Saki Malehi, Amal; Mahmoudi, Mandana (Frontiers in Public Health, 2022)
Aim: the aim of this study was to evaluate the effect of gel with amniotic fluid (AF) formulation on wound healing in diabetic foot ulcers. Methods: This triple blind clinical trial was performed on 92 type 2 diabetic patients referring to the Diabetes Clinic of Golestan Hospital of Ahvaz, southwest of Iran in 2019-2020. Patients were randomly divided into three groups of intervention and one placebo group. The wounds of the three intervention groups were dressed with gauze impregnated with AF formulation while wounds of the control group were dressed with plain gauze without any topical agent. Chi-square tests and generalized estimating equations (GEE) with a significance level of 0.05 were used to analyze the data. Results: At the end of the eighth week, there was a statistically significant difference between the four groups in terms of wound grade, wound color, condition of the tissues around the wound, the general condition of the wound, and the duration of wound healing (P <0.05). Discussion: From our experience with the patients in the present study, we believe that AF represents a useful and safe option for the treatment of chronic diabetic foot wounds. Trial registration: This investigation was registered in the Iranian Registry of Clinical Trials Center (IRCT20201010048985N1; Registration date: 18/11/2020).